Impact of Career Development and Leadership on Performance Employees with Job Loyalty as an Intervening Variable - Qodariyah, Lailatul (Journal of Business Management and Economic Development, 2023)
This study aims to determine whether career development and leadership have an impact on employee performance through work loyalty as an intervention variable or not. In this study, 100 respondents were used as a sample, calculated using the Slovin formula from 406 populations with a 5% margin of error. It collects data using a Likert scale and scores using a Questionnaire. The data analysis method used by researchers is a statistical test using SPSS version 23 using analytical techniques, classic assumption tests, path tests, coefficient of determination, and hypothesis testing. The results of this study suggest several steps that can be taken to improve performance among others by giving promotions to employees with good performance, the role of a leader who can arouse employee passion and obey and work loyally to improve employee performance.